2022
DOI: 10.3389/fped.2022.851700
|View full text |Cite
|
Sign up to set email alerts
|

The effects of birth spacing on early childhood development in high-income nations: A systematic review

Abstract: ObjectiveThis study aimed to systematically review the literature on the associations between birth spacing and developmental outcomes in early childhood (3–10 years of age). Studies examining the associations between interpregnancy intervals and child development outcomes during and beyond the perinatal period have not been systematically reviewed.MethodsWe searched Ovid/MEDLINE, Global Health, PsycINFO, EMBASE, CINAHL Plus, Educational Source, Research Starters, ERIC, Scopus, PubMed, Social Science Research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…This has been found in some studies (Buckles & Munnich, 2012;Karwath et al, 2014), but opposite patterns have also been reported, with the age gap being negatively correlated to cognitive outcomes (Gurgand et al, 2022;;non-significant trend in Havron et al, 2019). Mixed findings have also been reported in a systematic review (Dhamrait et al, 2022).…”
Section: Introductionmentioning
confidence: 72%
“…This has been found in some studies (Buckles & Munnich, 2012;Karwath et al, 2014), but opposite patterns have also been reported, with the age gap being negatively correlated to cognitive outcomes (Gurgand et al, 2022;;non-significant trend in Havron et al, 2019). Mixed findings have also been reported in a systematic review (Dhamrait et al, 2022).…”
Section: Introductionmentioning
confidence: 72%